2006
DOI: 10.1111/j.1748-720x.2006.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

The National Nanotechnology Initiative and the Social Good

Abstract: The purpose of the National Nanotechnology Initiative (NNI) is to promote nanotechnology in a way that benefits the citizens of the United States. It involves a commitment to support responsible development of nanotechnology. The NNI's enactment of this commitment is critically assessed. It is concluded that there are not adequate avenues within the NNI by which social and ethical issues can be raised, considered, and, when appropriate, addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…14 It is estimated that there are already more than 200 nanotechnology-based products in the consumer marketplace, see Wardak and Gorman [60]. 15 Compare the critical remarks concerning the US National Nanotechnology Initiative in Sandler and Kay [49] at 677-678; the Council for Science and Technology [55] paragraph 146; and, Einsiedel and Goldberg [19].…”
Section: The Precautionary Puzzlementioning
confidence: 93%
“…14 It is estimated that there are already more than 200 nanotechnology-based products in the consumer marketplace, see Wardak and Gorman [60]. 15 Compare the critical remarks concerning the US National Nanotechnology Initiative in Sandler and Kay [49] at 677-678; the Council for Science and Technology [55] paragraph 146; and, Einsiedel and Goldberg [19].…”
Section: The Precautionary Puzzlementioning
confidence: 93%
“…A key element in developing societal trust in the motives of actors involved with developing the products of novel technologies is to ensure that these actors take account of the concerns of interested stakeholder s (including the general public), and address these concerns in the process of research and policy formulation, as well as in considering potential commercialization strategies [9] . Activities geared toward involving the public have, in the agri -food sector, ranged from traditional consultations (e.g., quantitative surveys of nationally representative populations) and focus groups conducted in order to evaluate citizen views, through to exercises specifi cally focusing on citizen involvement in the decision -making process.…”
Section: What Is " Public Engagement " ?mentioning
confidence: 99%
“…This is particularly the case with nanotechnology, where increased participation (particularly early in the process, or " upstream " ) has been prescribed by a major inquiry into nanotechnologies in the UK conducted by the Royal Society and Royal Academy of Engineering (see reference [23] for a description), and has been encapsulated in the major National Nanotechnology Initiative ( NNI ) in the USA [9] .…”
Section: What Is " Public Engagement " ?mentioning
confidence: 99%
“…Research into social and ethical dimensions of nanotechnologies attracts little resources from government and industry, leaving us with little understanding of these complex issues. In their evaluation of the National Nanotechnology Initiative (NNI), Sandler and Kay (2006) found 4 per cent of funding (or US$48 million) was directed towards ethical, legal and social (ELS) research, representing the minimum legal requirement for ELS research under the 21st Research and Development Act (Public Law 108-153). They also found that social research that was funded through the NNI was directed into building public support and acceptance of nanotechnology, rather than deepening public understanding and engagement in nanotechnology debates, or directing nanotechnology applications towards the public good.…”
Section: Agri-food Nanotechnologies and Their Social Impacts For Ruramentioning
confidence: 99%